(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2023)
Background. Nitrate is one of the common contaminants in food. Potentiometry has a short response time and low requirement of sample preparation, high selectivity and sensitivity, ease of operation, and miniaturization. So, it is a promising method for the rapid detection of nitrates in various environmental matrices. An all-solid-state ion-selective electrodes based on modified carbon paste possess advantages such as ease of preparation and regeneration, stable response, and low Ohmic resistance. makes it a suitable anion exchanger. Therefore, a carbon paste electrode modified with such quaternary ammonium salt adsorbed onto silica gel could show a good response to nitrates. Methods. The properties of the prepared electrode were studied by the potentiometric method according to the IUPAC recommendations. The potential of the investigated electrode, measured relative to the 3,5 M silver chloride reference electrode, was used as an analytical signal. Results. The electrode proposed was fully characterized in terms of composition, response time, ionic strange, and usable pH range. The electrode with mass ratio carbon: modifier 1: 5 exhibits linear response to nitrate species in the range of 1,5⋅10-1 to 1⋅10-5 mol/l with Nernstian slope of 0,062 ± 0,007 V per decade of nitrate concentration and detection limit of 1 ⋅10-5 mol/l. The analytical response of the electrode to nitrate remains constant in the pH range of 2,5 to 9,8 and in the presence of 1 ⋅ 10-3 to 0,2 mol/l KCl. The response of the electrode reaches its equilibrium value within 25 s after immersing the electrode in nitrate solution with a concentration of 1⋅10-7 to 1⋅10-5 mol/l and 15 s in the solution of 1⋅10-3 to 1 ⋅10-1 mol/l. Selectivity coefficients showed chloride anions have minimal interfere with the electrode function. The electrode was used for the determination of nitrate in vegetables using the direct potentiometry method. The validation of results was proved by the reference method and satisfactory results were obtained. Conclusions. A nitrate-selective electrode based on carbon paste with the addition of quaternary ammonium salt immobilized on the surface of silica gel is proposed. It was established that the modifier gives the electrode an anionic function. Given the high selectivity, sensitivity, and speed of response, the developed electrode is suitable for the determination of nitrates in drinking water of various mineralization and vegetable products after minimal sample preparation.